ANALISIS KENDALA PBB (PERSERIKATAN BANGSA-BANGSA) DALAM MEMBERIKAN SANKSI HUKUMAN DI TINJAU DARI ICJ (INTERNATIONAL COURT OF JUSTICE) - Hartana; Ni Kadek Astrina Desiana (Jurnal Pacta Sunt Servanda, 2020)
The state returned to traditional mechanisms to prevent war, new attempts to end the prohibition on the use of force failed, in the end. The Russian Federation did not extend the superpower status of the Soviet Union, therefore the three groups of countries also ceased to exist. Former socialist countries, divided, tend to rely on Western countries. Developing countries appear to be no longer driven by ideology, but are united by demands for more international economic and financial assistance and greater access to world markets. The United Nations itself, as a mechanism for maintaining peace and stability, has been in relative decline, while states have shown a tendency to strengthen the role of military alliances such as NATO and tendencies towards regionalization, and terrorism has gradually dictated changes in certain categories of international law, such as self-defense. It is a fact that states have more than one possibility open within the United Nations in the event of aggression, but the countless flaws of this mechanism cannot be discounted. Improving functioning UN mechanisms in general, but also mechanisms whereby state responsibilities are carried out efficiently and where states will fulfill their obligations is an urgent need, to underpin the credibility of institutions and mechanisms, and for the international community as a whole. Moreover, whether or not member states are willing to eventually step up and take responsibility for efficient mechanisms in terms of maintaining international peace and security remains to be seen.